Leadership skills - Rossiter, Diane E.; Ferguson Publishing (New York : Ferguson, 2009)
'Understanding the role of a leader in the work environment can make the work experience more rewarding and satisfying. By establishing the importance of leaders in almost any group dynamic, Leadership Skills, Third Edition helps students understand the qualities of all successful leaders, such as courteousness, compassion, decisiveness, and willingness to give and receive criticism.'--Amazon.com.
Rev. ed. of : Leadership skills / by Diane E. Rossiter, 1998
Includes bibliographical references (p. 151-156) and index
Keywords: Leadership -- Juvenile literature; Management -- Juvenile literature; Teams in the workplace -- Juvenile literature; Vocational guidance -- Juvenile literature; Leadership; Management; Teams in the workplace; Vocational guidance